Added-Value and Development Strategy of Arabica Coffee Manufacturing Business - Siti Fatimah Erniasari; Siswanto Imam Santoso; Mukson Mukson (SOCA: Jurnal Sosial Ekonomi Pertanian, 2021)
The manufacturing business of Arabica Coffee highly potential in increasing the selling value of the coffee commodity. Unfortunately, this business still faces some hindrances during its implementation. This study aimed to: (1) analyze the amount of added-value in the manufacturing process of Arabica Coffee and (2) analyze the development strategy required. The study conducted from December 2019 to February 2020 in six Arabica Coffee Manufacturing businesses in Tlahab Village. This case-study was involving 12 respondents and employing Hayami Method, IFAS matrix, EFAS matrix, and SWOT matrix as the data analysis method. Result showed that the mean of the added-value of the green bean and coffee powder, green-bean coffee and the coffee powder was IDR 3,425.44 and IDR 16,916.05, 26.45% (moderate added value) and 54.94% (high added value), respectively. The analysis from the IFAS and EFAS matrix resulted six factors of strength, five factors of weakness, five factors of opportunity, and three factors of threat. According to the SWOT diagram, the Arabica Coffee manufacturing business in Tlahab Village was in Quadrant I that indicated the strategy required was using the strength and utilizing the opportunities existed. Those strategies consisted of the utilization of all resources in Tlahab Village, improving cooperation between the stakeholder and business owner, and developing the marketing management used.